Pemasangan Panel Surya Sebagai Energi Alternatif di Pesantren Darul Hikmah, Kabupaten Aceh Besar - Rahmawati, Cut; Muhtadin, Muhtadin; Mahyuddin, Mahyuddin; Lindawati, Lindawati; Effendy, Amalia; Noviandy, Teuku Rizky; Sufri, Rahmat; Anisah, Anisah; Faisal, Muhammad; Mutaqin, Raihan; Fatani, Muhammad; Alfharijy, Muhammad Daffa (ABDIMASKU : Jurnal Pengabdian Masyarakat UTND, 2025)
This activity aims to provide students with an understanding of the importance of renewable energy usage and to raise awareness about sustainability. It took place at the Darul Hikmah Islamic Boarding School located in Geundring Village, Darul Imarah District, Aceh Besar Regency. The methodology employed included socialization, discussions, and practical training on solar panel installation. Participants comprised a team from the Faculty of Engineering at Abulyatama University and students from Darul Hikmah Islamic Boarding School.The outcomes of this initiative include the successful dissemination of information regarding the benefits of solar panels as an alternative energy source, as well as the installation of one solar-powered lamp that can provide lighting at night and enhance the quality of the boarding school’s facilities. The students gained a better understanding of renewable energy through socialization and discussions. They learned about the benefits and operation of solar panels and the significance of environmental sustainability. This activity contributed to raising the students' awareness of the need to transition to more environmentally friendly energy sources, thereby potentially stimulating further renewable energy initiatives.